Adjuvant therapies in advanced hepatocellular carcinoma: moving forward from the STORM. Issue 1 (December 2016) - Bouattour, Mohamed; Soubrane, Olivier; de Gramont, Armand; Faivre, Sandrine
Abstract Like other previous treatments and approaches, sorafenib, an antiangiogenic drug, failed to show any benefit in the adjuvant setting for hepatocellular carcinoma in a large clinical trial. We discuss reasons and implications of these negative results and the implications for clinical practice and future research. Trial registration ClinicalTrials.gov:NCT00692770 . Registered 5 June 2008. This study has been completed.